An Adaption of Human-Induced Hepatocytes to In Vitro Genetic Toxicity Tests. (24th December 2018) - Liu, Weiying; Xi, Jing; Cao, Yiyi; You, Xinyue; Chen, Ruixue; Zhang, Xinyu; Han, Li; Pan, Guoyu; Luan, Yang
Abstract: Metabolic activation is essential in standard in vitro genotoxicity test systems. At present, there is a lack of suitable cell models that can express the major characteristics of liver function for predicting substance toxicity in humans. Human-induced hepatocytes (hiHeps), which have been generated from fibroblasts by lentiviral expression of liver transcription factors, can express hepatic gene programs and can be expanded in vitro and display functional characteristics of mature hepatocytes, including cytochrome P450 enzyme activity and biliary drug clearance. Our purpose was to investigate whether hiHeps could be used as a more suitable model for genotoxicity evaluation of chemicals. Therefore, a direct mutagen, methylmethanesulfonate (MMS), and five promutagens [2-nitrofluorene (2-NF), benzo[a]pyrene (B[a]P), aflatoxin B1, cyclophosphamide and N-nitrosodiethylamine] were tested by the cytokinesis-block micronucleus test and the comet assay. Results from genotoxicity tests showed that the micronucleus frequencies were significantly increased by all of the six clastogens tested. Moreover, MMS, 2-NF and B[a]P induced significant increases in the % Tail DNA in the comet assay. In conclusion, our findings from the preliminary study demonstrated that hiHeps could detect the genotoxicity of indirect carcinogens, suggesting their potential to be applied as an effective tool for in vitro genotoxicity assessments.